Effective Factors On Staffs' Job Satisfaction Based On Herzberg Theory In Qazvin Teaching Hospitals - Amir Ashkan Nasiripour; Bahram Delgoshaie; Rohollah Kalhor; Mohammad Zakaria Kiaei; Elham Shahbahrami; Seyed Saeed Tabatabaee (Tehran University of Medical Sciences, 2013)
Background and Aim: The Effectiveness and success of an organization depends on two factors one is the employees' Performances and the other is the level of understanding between managers and employees in prioritize of different job motivators. The aim of this study was to determine factors that affect staffs' performances in Qazvin teaching hospitals based on the Herzberg's theory. Materials and Methods: This research was a descriptive study. To achieve the main aim of this study, one hundred and ten employees were selected through a multi- stage sampling method .In this study, for data collection a self-report questionnaire was used. The five-point Likert scale was used to determine the degree of importance of any hygiene and multinational's factors affecting the performance of the employees. Results: Among hygiene factors, the prevailing place was for Job security with an average 4/39 and then followed by a suitable salary with an average 4/38 of 5 scores. Among multinational's factors, job responsibility with an average 4/38 and job interest with an average 4/38 were placed as the most important factors in employees' performance. %70/8 employees mentioned that two factors of suitable salary and job security are the most important obstacle for improvement of employee's performance. Conclusion : The data of this study reveals that, Attention and Planning in providing  proper salary and job security as hygiene factors and sense of responsibility and success as motivational factors, may play a more effective role in improving employees' performance than any other factors.